2012
DOI: 10.1001/archgenpsychiatry.2012.913
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Modulation of Neural Activity by Emotion in Youth With Bipolar Disorder, Youth With Severe Mood Dysregulation, and Healthy Volunteers

Abstract: Context Youth with bipolar disorder (BD) and those with severe, non-episodic irritability (severe mood dysregulation, SMD) show amygdala dysfunction during face emotion processing. However, studies have not compared such patients to each other and to comparison subjects in neural responsiveness to subtle changes in face emotion; the ability to process such changes is important for social cognition. We employed a novel parametrically designed faces paradigm. Objective Using a parametrically morphed emotional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
70
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 51 publications
12
70
3
3
Order By: Relevance
“…18 Another study demonstrated that, while participants with BD and SMD exhibited similar deficits in amyg dala modulation in response to facial expressions of increasing anger intensity, the 2 patient groups exhibited different patterns of abnormalities in ventral visual pathway and frontoparietal activity. 17 Future work combining functional magnetic resonance imaging and eye tracking is needed to elucidate associations among neural dysfunction, impaired eye gaze and facial emotion labelling deficits in children with BD and SMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Another study demonstrated that, while participants with BD and SMD exhibited similar deficits in amyg dala modulation in response to facial expressions of increasing anger intensity, the 2 patient groups exhibited different patterns of abnormalities in ventral visual pathway and frontoparietal activity. 17 Future work combining functional magnetic resonance imaging and eye tracking is needed to elucidate associations among neural dysfunction, impaired eye gaze and facial emotion labelling deficits in children with BD and SMD.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to SMD, the neural dysfunction data are considerably more limited, although data do suggest both amygdala and parietal dysfunction. 17,18 The examination of visual scan patterns of emotional faces has been important to elucidate precise pathophysiological mechanisms of the aberrant face labelling behaviours across psychiatric disorders. In people with autism, [19][20][21][22] psychopathy 23 and schizophrenia, [24][25][26][27] each in comparison with healthy controls only, eye tracking studies have revealed associations between emotion labelling deficits and decreased attention to eyes.…”
Section: Introductionmentioning
confidence: 99%
“…The research on SMD focused on the differentiation from BD, and neuropsychological and imaging data comparing the two entities clarified its boundaries. 26,27 Furthermore, research on SMD stressed the importance of chronic irritability for developmental psychiatry and suggested its adoption by the DSM-5. In an epidemiological sample, lifetime prevalence for SMD was 3.3%.…”
Section: Chronic Irritability Temper Outbursts and Disruptive Mood mentioning
confidence: 99%
“…Actual literature suggests that changes in parietal activity in networks involving the amygdala might underlie dysfunctional affective processing [76].…”
Section: Discussionmentioning
confidence: 99%